2003
DOI: 10.1039/b208871a
|View full text |Cite
|
Sign up to set email alerts
|

Through-space interactions between face-to-face, center-to-edge oriented arenes: importance of polar–π effects

Abstract: Two series of conformationally restricted polycyclic compounds (1-3 and 4-7) have been synthesized as model systems for studying the through-space interactions between face-to-face, center-to-edge (parallel-offset) oriented arenes. These compounds feature different X substituents on one of the interacting rings. By monitoring the variation of the delta Gz for the rotation around the aryl-aryl bond in 1-7 as a function of X by 2D [1H,1H] EXSY NMR spectroscopy, it was found that the barriers increase on passing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 89 publications
5
91
0
2
Order By: Relevance
“…[36] Seit den bahnbrechenden Arbeiten von Ō ki [67] haben sich Triptycenderivate [68] [70] Analog zu deren früherem 1,8-Diarylnaphthalin-Modellsystem [71] nahm die Rotationsbarriere (DG°) in beiden Serien mit zunehmend elektronenziehenden Substituenten zu. Eine ausgezeichnete Korrelation mit den Hammett-Parametern s p wurde gefunden, was die Rolle der polaren p-Effekte unterstreicht.…”
Section: Modellstudienunclassified
“…[36] Seit den bahnbrechenden Arbeiten von Ō ki [67] haben sich Triptycenderivate [68] [70] Analog zu deren früherem 1,8-Diarylnaphthalin-Modellsystem [71] nahm die Rotationsbarriere (DG°) in beiden Serien mit zunehmend elektronenziehenden Substituenten zu. Eine ausgezeichnete Korrelation mit den Hammett-Parametern s p wurde gefunden, was die Rolle der polaren p-Effekte unterstreicht.…”
Section: Modellstudienunclassified
“…For the sake of simplicity, these can roughly be considered as belonging to the types of arrangements reported in Scheme 1 for the paradigmatic case of two interacting benzene rings: the parallel stack (PS), the parallel offset (PO), and the edge-to-face (EtF) dispositions (the EtF disposition can be specified as tilted or orthogonal depending on the angle between the planes of the rings). [9b] In previous studies on model systems, we experimentally determined the strength and nature of the interactions between differently substituted arenes in the PS [10] and PO [11] dispositions. An important part of our work has been devoted to determining how the replacement of one of the two interacting rings with a heavily fluorinated arene (in short, ArF) influences the PS and PO interactions, both in solution [11,12] and in the crystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…[9b] In previous studies on model systems, we experimentally determined the strength and nature of the interactions between differently substituted arenes in the PS [10] and PO [11] dispositions. An important part of our work has been devoted to determining how the replacement of one of the two interacting rings with a heavily fluorinated arene (in short, ArF) influences the PS and PO interactions, both in solution [11,12] and in the crystalline state. [13,14] In this paper we report the results of an investigation aimed at understanding how the extensive fluorination of Abstract: Simple model systems based on the [3,3]metaparacyclophane skeleton have been designed to study the effect of fluorination of the "face" ring on the edge-to-face (EtF) interactions with the C Ar À H bond of a phenyl ring or the nitrogen lone-pair of pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been reported that aryl rotation is responsible for spectral changes and rotation affected by space interaction (Polar-π interaction). [26] In order to study the rotational barrier, we carried out X-ray analysis of compound 2b. [24] This molecule has two advantages: (i) the size of one of the aryl groups is as bulky as in 4b and 4c, (ii) the ''O'' atoms in the pyran ring may effectively participate in intramolecular CϪH···O interactions.…”
Section: Resultsmentioning
confidence: 99%